Conceptual model of sustainable tourism for the correction of San Basilio de Palenque department of Bolivar Colombia (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
The aim of the project is to design a model of sustainable tourism for the village of San Basilio de Palenque - Bolivar, that allows a better development of tourism in the destination. The type of research is descriptive, a structured survey instrument was applied 67 inhabitants of the population, the model took into account the economic dimensions: It assures that the development of economic activities in the destination are viable in the long-term and report benefits to all people interested. Environmental: It seeks for an optimal use of environmental resources, maintaining essential ecological processes. Sociocultural: It preserves its cultural heritage as a whole. For its validation, the principles of sustainability of the World Tourism Organization and the requirements of the Colombian sectorial technical standard which set the guidelines for a sustainable tourist destination were taken as reference
Keywords: model tourism; economic sustainability; environmental sustainability; cultural sustainability